The perceptions on group work among Malaysian pre-university gifted students - Faieza Samat; Normahirah Nek Abd Rahman (Penerbit Universiti Kebangsaan Malaysia, 2019)
Gifted students have intense motivation to explore ideas and difficult problems in detail and in depth, and if they have also confidence and good communication skills, gifted students will become the most valuable asset to the community. Other than that, communication skills are essential for the students to interact effectively with other students with diverse cognitive ability during their pursuit to higher education. Thus, this paper investigates the perception of pair or group work among a group of Malaysian pre-university gifted students in Vector Calculus course. Instrument used in this study is an open-ended questionnaire. Results show that most students view Vector Calculus as a hard course. They perceive group work as good and helpful other than it affects the way they learn. On the other hand, some students have negative view on group work indicating the giftedness quality among them. Thus, it is suggested for educators to carefully employ grouping strategies to cater Malaysian pre-university gifted students especially in a hard course.